2013
DOI: 10.1007/s13191-013-0273-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Aesthetic Full Mouth Rehabilitation of a Severely Worn Dentition to Restore Vertical Dimension: A Case Report

Abstract: Deterioration or malfunction of any part should be viewed as an effect that has the direct or indirect result of one or more identifiable cause. The establishment of definitive goals is the foundation for the full mouth rehabilitation. Severe wear is common in prosthodontic patients whose teeth have been held in functional interference for long period of time. This case report presents a description of a patient's oral rehabilitation with metal ceramic restorations to increase vertical dimension while achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Polyvinyl siloxane impression material is the material of choice of making the impressions for various clinical situations for making implant impressions, single tooth impression, fixed partial denture impressions, full mouth rehabilitation cases etc. [ 29 ] It has been used as it produces dimensionally accurate impressions. Lacy et al [ 30 ] conducted a quantitative comparison of the accuracy and dimensional stability of representative products in each class of polyether, polysulfides, and PVS and showed that PVSs are the most stable of elastomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyvinyl siloxane impression material is the material of choice of making the impressions for various clinical situations for making implant impressions, single tooth impression, fixed partial denture impressions, full mouth rehabilitation cases etc. [ 29 ] It has been used as it produces dimensionally accurate impressions. Lacy et al [ 30 ] conducted a quantitative comparison of the accuracy and dimensional stability of representative products in each class of polyether, polysulfides, and PVS and showed that PVSs are the most stable of elastomers.…”
Section: Discussionmentioning
confidence: 99%
“…Lacy et al [ 30 ] conducted a quantitative comparison of the accuracy and dimensional stability of representative products in each class of polyether, polysulfides, and PVS and showed that PVSs are the most stable of elastomers. Although Aquasil has been used from decades to record accurate impressions,[ 29 30 ] its efficacy as retraction agent has not been tested till date.…”
Section: Discussionmentioning
confidence: 99%
“…One of the method for increasing OVD by providing temporary bridges at an increased OVD for minimum 4-6 weeks. This was done to accustom temporomandibular joint to the new OVD dimension and to prevent technical complication in newly placed indirect restoration (20,21). Our patient had moderate loss of occlusal vertical dimension (OVD that was uncompensated with freeway space of 4-5mm along with anterior deep bite.…”
Section: Discussionmentioning
confidence: 97%
“…The shape and function of masticatory apparatus should be restored as close to normal as possible. Full-mouth rehabilitation can be categorized into three groups based on clinical and laboratory techniques when both arches are restored at the same time (1). Simultaneous restoration of both arches is done (2).…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of each quadrant is carried out according to a programmed manner (3). A combination of both can be done (1). presence of temporomandibular joint disorders or developmental anomalies are all signs that a new approach needs to be taken (3,4,5).…”
Section: Introductionmentioning
confidence: 99%